(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Wound healing is a complex biological process. The study focuses on Ehretia laevis Roxb. (Khandu chaka) For its wound healing, antimicrobial and anti-inflammatory properties. Wound healing is multifaceted process. Plant extract generally contains various bioactive compounds; methanol extract contains flavonoids tannins and napthoquinones derivatives while chloroform extract contains baurenol in addition to above. The bioactive compounds can be configured using FTIR and TLC. The film forming spray overcomes the problems associated with conventional wound healing products. Hydroxyl propyl methyl cellulose k100 (HPMC) is used as a film forming polymer and poly ethylene glycol (PEG 400) is used as plasticizer. The spray creates a flexible, waterproof and protective layer. The pharmaceutical and pharmacological evaluation of spray is performed. Pharmaceutical evaluation includes density, viscosity pH, film durability etc. pharmacological evaluation is done using albino-wister rat. Formulation 1 significantly shows more wound contraction study as compared to formulation 2 and control group. The activity of formulation is evaluated using standard cipladin. The study bridges the traditional knowledge with modern pharmaceutical innovations.